Effects of Dietary Nutrient Density on Performance and Carcass Quality of Male Broilers Grown for Further Processing - Saleh, E.A.; Watkins, S.E.; Waldroup, A.L.; Waldroup, P.W. (International Journal of Poultry Science, 2003)
Two trials of identical design were conducted in floor pens to characterize the response of male broilers grown to heavy weights for further processing to dietary nutrient density levels. Nutrient density is defined as the metabolizable energy content of the diet with all essential nutrients maintained in proportion. Ten treatments were utilized with varying nutrient densities obtained by adding poultry oil from 0 to 9% in increments of 1%. Crude protein, amino acids, and other essential nutrients were maintained in proportion to dietary energy levels. Body weights, feed consumed and processing quality were obtained at different intervals up to 63 days of age. Body weight peaked with the diet containing 6% added fat (3267 ME Kcal/ kg, mean of starter, grower, and finisher ME values). Feed intake tended to decrease with increasing nutrient density, but not at a rate commensurate with the change in energy levels. Feed conversion (g gain per g feed) improved as dietary nutrient density increased. Dressing percentage tended to decrease as dietary nutrient density level increased. Abdominal fat and breast meat, both on an absolute weight or percentage of carcass weight basis, remained rather constant when protein was maintained in proportion to energy.